2012
DOI: 10.1007/s11250-012-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Grewia oppositifolia leaves as crude protein supplement to low-quality forage diets of sheep

Abstract: In the tropical arid and semi-arid regions of many developing countries, sheep are predominantly grazed on low-quality pastures and stall-fed on crop residues. This study evaluated the potential of Grewia oppositifolia tree leaves as crude protein (CP) supplement to the low-quality diets of sheep in comparison with cottonseed cake (CSC). Changes in the chemical composition of the leaves with progressive maturation (December to March) were studied. The leaves maintained a high CP content (>164 g/kg dry matter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The amount (g/day) of N retained in the body increased significantly (P<00.01) from 2.34 to 14.45 g/day with the substitution of elephant grass with Z. tetragona (Table 2). This findings suggest that the additional N supplied by Z. tetragona forage was efficiently utilised and resulted in a greater N retention as also recently found by Khan and Habib (2012) using peanut (Arachis hypogaea) forage. Apparent in vivo digestibility of DM and CP showed that in sheep fed Z. tetragona the CP digestibility was improved (P=0.003), whereas DM digestibility was unaffected by dietary treatment.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The amount (g/day) of N retained in the body increased significantly (P<00.01) from 2.34 to 14.45 g/day with the substitution of elephant grass with Z. tetragona (Table 2). This findings suggest that the additional N supplied by Z. tetragona forage was efficiently utilised and resulted in a greater N retention as also recently found by Khan and Habib (2012) using peanut (Arachis hypogaea) forage. Apparent in vivo digestibility of DM and CP showed that in sheep fed Z. tetragona the CP digestibility was improved (P=0.003), whereas DM digestibility was unaffected by dietary treatment.…”
Section: Resultssupporting
confidence: 80%
“…This reflects both the potentially lower production costs per unit of energy associated with some alternative forage crops and the ability of some of these crops to increase total dry matter (DM) intake and improve animal productions (Khan and Habib, 2012;Tufarelli et al, 2012). Leaves of browse species are potential source of nutrients that could be used to improve the production of ruminants consuming tropical pastures of low nutritive value (Barakat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Forages, in fresh or conserved form (hay and silage), are a natural, and often a major, source of low‐cost nutrients for ruminant livestock under most dietary regimes, and as such the efficient utilization of this resource can improve farm profitability and provide long‐term sustainability for all types of livestock production systems 1 . The pastures in the natural rangelands of northern Pakistan are a major source of feed and nutrients for grazing livestock – particularly those raised under the transhumant, nomadic, and sedentary farming systems 2‐4 . However, as in other (sub)‐tropical developing countries, the quantity and quality of pastures in natural rangelands are declining due to consistent overgrazing and recurrent droughts.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock production, and the small-holding and the extensive grazing (transhumant, nomadic and sedentary farming) livestock production systems in Pakistan lack long-term sustainability, due to declining quantity and quality green forages and pastures, particularly during extended summer and winter dry periods (Khan and Habib, 2012;Khan et al, 2015b). Moreover, the conventional concentrates such as oilseeds and cereal grain byproducts are increasingly becoming scarce and expensive, and most of the smallholder subsistence farmers could not afford to feed high-cost commercial concentrates to their animals for a longer period (Habib et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%